2018
DOI: 10.4103/sja.sja_760_17
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal dexmedetomidine as an adjuvant to bupivacaine for postoperative pain management in children undergoing laparoscopic appendectomy: A prospective randomized trial

Abstract: Background and Aims:Intraperitoneal local anesthetic is an effective analgesic approach in laparoscopic appendectomy in adults. The aim of the study was to compare the postoperative pain when intraperitoneal bupivacaine is administered alone versus the addition of dexmedetomidine to it in children undergoing a laparoscopic appendectomy.Methods:In this prospective randomized trial, 52 children were randomly allocated to Group B who received intraperitoneal bupivacaine 0.25% (2 mg/kg) or Group BD who received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The 17 included papers were published between 1996 and 2020, and virtually all mentioned different approaches to the treatment of POP in children with LA, i.e., lidocaine infusion, different analgesic approaches, ultrasound-guided transverse abdominis block (UGTAP), ultrasound-guided quadratus lumborum block (UGQLB), and comparison of open appendectomy (OA) with LA in relation to the treatment of POP in children [ 7 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. As shown in Table 1 , a total of 1754 samples were included in the study, of which 61.86% were male.…”
Section: Resultsmentioning
confidence: 99%
“…The 17 included papers were published between 1996 and 2020, and virtually all mentioned different approaches to the treatment of POP in children with LA, i.e., lidocaine infusion, different analgesic approaches, ultrasound-guided transverse abdominis block (UGTAP), ultrasound-guided quadratus lumborum block (UGQLB), and comparison of open appendectomy (OA) with LA in relation to the treatment of POP in children [ 7 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. As shown in Table 1 , a total of 1754 samples were included in the study, of which 61.86% were male.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated dexmedetomidine as an adjuvant to IPLA in laparoscopic surgeries to improve postoperative pain scores and decrease post-operative analgesic consumption. 10,13,22 We defined the duration of analgesia as the time period from the administration of the drug to the requirement of rescue analgesia that is a VAS score of ≥4. The mean time to first request of analgesia in this study was found significantly more in the Group-IV (216.467±42.198 min) compared to the Group-IP (108.033±48.779 min).…”
Section: Discussionmentioning
confidence: 99%
“…• Time to first request of analgesia was noted, considering the time of administration of study drug as "Time 0" • The post-operative pain intensity was assessed using visual analogue score (VAS) 12 where 0=no pain and 10=worst pain imaginable • Level of sedation was assessed using the Ramsay sedation scale 11 (RSS) where (1) anxious and agitated or restless, or both, (2) cooperative and oriented, (3) responds to commands only, (4) brisk response to light glabellar tap or loud auditory stimulus, (5) sluggish response to light glabellar tap or loud auditory stimulus, and ( 6) no response • Patient's satisfaction was assessed using the 7-point Likert scale: 13 ( 1) Extremely dissatisfied, (2) dissatisfied, (3) somewhat dissatisfied, (4) undecided, (5) somewhat satisfied, (6) satisfied, and (7) extremely satisfied.…”
Section: Group-ipmentioning
confidence: 99%
“…Various additives could be used to prolong the duration of analgesia produced. [ 24 ] This should be studied further to see if there is an increased benefit to patients.…”
Section: Discussionmentioning
confidence: 99%